Preparation method and application of modified porous ceramsite with slow release function
By modifying the porous ceratops with polylactic acid to form a sustained release layer, the problems of insufficient surfactivity and alkalinity of traditional porous ceratops are solved, and the good interaction between the ceratops and nutrient solution and the promotion of plant growth are achieved.
Patent Information
- Application Number
- CN202411872320.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
AI Technical Summary
Traditional porous ceramic particles lack surfactivity during use, making them difficult to effectively interact with plant nutrients and nutrient solution, and their alkalinity limits the plant's absorption efficiency of nutrients.
By mixing polylactic acid with citric acid, an acidic solution is formed to modify the porous ceratops to form a sustained release layer to maintain the acidity of the surface of the ceratops, improve its affinity with the nutrient solution, and extend the stability of the modification.
The modified porous ceramide can maintain a suitable pH value in the aqueous solution for a long time, promote plant growth, improve the efficiency of water and nutrient utilization in plant roots, and reduce the frequency of modification and maintenance costs.
Smart Images

Figure CN119684035A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a slow-release acidic modification method for porous ceramic particles and application of the method in water bodies. Background Art
[0002] With the continuous growth of the global population and the intensification of environmental pollution, agricultural production faces serious challenges. In particular, the shortage of water resources and soil degradation have prompted scientists to continuously explore efficient and environmentally friendly agricultural cultivation technologies. Among them, soilless cultivation technology has received widespread attention and application due to its advantages such as high efficiency in water resource utilization and avoidance of soil disease transmission. In soilless cultivation, the cultivation matrix is one of the key components, and its main function is to fix the plant roots and provide necessary water and nutrients. At present, porous ceramic particles are widely used in soilless cultivation due to their light texture, high porosity, and good chemical stability. Porous ceramic particles, especially with their high specific surface area and high mechanical strength, perform well in plant root fixation, air permeability, and water retention, making them ideal matrix materials in soilless cultivation. However, traditional porous ceramic particles also expose some defects during use. For example, their surface activity is insufficient, their ability to interact with plant nutrients and nutrient solution is not strong, and their alkalinity limits the efficiency of plant absorption of nutrients. In order to solve this problem, researchers have been committed to modifying porous ceramic particles through various methods in recent years to improve their surface activity and affinity with nutrient solution. The sustained-release technology can control the release rate of active ingredients so that they are gradually released within a specific time, thereby achieving the purpose of prolonging the effect and reducing resource waste.
[0003] For example, in patent CN110698225A, a mixture of dilute hydrochloric acid and ferric chloride is used to modify porous ceramsite to make it have a lower pH, and Fe 3+ The ceramsite is modified in a way that increases the isoelectric point of the ceramsite surface. The dissolved substances also increase the potential in the water body, thereby neutralizing the algae in the water body, thereby destabilizing it and achieving the effect of flocculating and settling the algae. However, dilute hydrochloric acid is a strong acid, which requires extra steps to neutralize it, and the effect is greatly reduced and a low pH cannot be maintained for a long time. Summary of the invention
[0004] In order to solve the deficiencies of the prior art, the present invention aims to provide a preparation method and a use method of modified porous ceramsite with a sustained-release function.
[0005] The above technical objectives of the present invention are achieved through the following technical solutions:
[0006] The first aspect of the present invention provides a method for preparing a modified porous ceramsite with a sustained-release function, comprising the following steps:
[0007] S1 pretreatment: pretreating the ceramsite to obtain pretreated ceramsite.
[0008] S2 modification: polylactic acid is added to a mixed solvent of dichloromethane and ethanol and stirred to obtain a polylactic acid solution; then citric acid is added to obtain an acidic mixed solution, which has the following beneficial effects: (1) the pretreated ceramsite will continuously dissolve alkaline substances in the aqueous solution, and the acidic mixed solution can maintain the pH of the aqueous solution at 4.0-6.5, and by changing the amount of citric acid added, the ceramsite can be changed to different acidity ranges to better meet the requirements of plant growth; (2) polylactic acid wraps the citric acid molecules and is coated on the surface of the porous ceramsite to form a sustained-release layer, thereby maintaining the long-term stability after modification.
[0009] S3 attachment: the mixed solution is intermittently allowed to stand and stirred at a uniform speed to ensure that the ceramsite and the polylactic acid solution are fully contacted and attached, and then separated to obtain attached ceramsite; wherein, after the mixed solution is allowed to stand for 2 hours each time, it is stirred at a uniform speed of 90r / min for 2 minutes.
[0010] S4 post-treatment: The attached ceramsite is left to stand and then dried to obtain a porous ceramsite product. The ceramsite is modified in S1; the ceramsite is washed with water; the washed ceramsite is placed in water and ultrasonicated for 20 minutes; finally, the ultrasonic ceramsite is dried to obtain the pre-treated ceramsite.
[0011] In S2, the concentration of polylactic acid is 10 to 50 g / L.
[0012] In S2, the stirring speed is 120-200 r / min, and the stirring time is 10-20 min.
[0013] Through the above technical solution, the stirring speed and time are limited, thereby achieving the effect of ensuring that the pretreated ceramsite and the polylactic acid solution are fully in contact.
[0014] In S2, the concentration of citric acid is 0.01 to 10 g / L.
[0015] In S4, the drying temperature is 50-100°C.
[0016] The invention also proposes an application of the porous ceramsite prepared by the method in balancing the pH value of water.
[0017] Beneficial Effects
[0018] The invention introduces polylactic acid loaded with citric acid to modify the ceramsite, so that the ceramsite is loaded with a slow-release layer, thereby keeping the pH of the ceramsite in a suitable environment for a long time, thereby promoting the growth of, for example, plants.
[0019] The polylactic acid coating in the present invention can improve the hydrophilicity and water retention of the porous ceramsite, so that it has better adsorption and retention effects on the nutrient solution, thereby improving the utilization efficiency of water and nutrients by the plant root system. Polylactic acid is a biodegradable material that can slowly degrade in the environment, thereby gradually releasing the loaded citric acid. This slow-release effect can extend the effective action time of citric acid, reduce the frequency of modification and maintenance costs, and has almost no negative impact on the environment, which meets the requirements of modern agriculture for green environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The curve diagram of pH change of ceramsite soaking water treated with polylactic acid-citric acid mixed solution over time; Figure 2 Curve of pH change of ceramsite soaking water after citric acid solution treatment over time: DETAILED DESCRIPTION
[0021] The method provided by the present invention will be further described by the following examples. The described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. The protection scope of the present invention is not limited to the embodiments, and all technical solutions under the ideas of the present invention should belong to the protection scope of the present invention.
[0022] Example 1
[0023] A method for preparing modified porous ceramsite with sustained-release function:
[0024] S1. Pretreatment: screen porous ceramsite with a particle size of 2 mm, and wash the powder on the surface of the ceramsite with distilled water until the washing liquid is clear and free of impurities; weigh a certain amount of ceramsite and immerse it completely in distilled water, place it in an ultrasonic device, and ultrasonicate it for 30 minutes. During this period, stir it at a constant speed of 1 minute every 10 minutes, and the stirring speed is 90r / min; finally, put the ultrasonicated ceramsite into an oven and bake it at 100°C for 1 hour to obtain pretreated ceramsite;
[0025] S2. Modification: Preparation of polylactic acid coating solution: 5 g of polylactic acid was added to a mixed solvent of 100 ml of dichloromethane and ethanol and stirred to obtain a polylactic acid solution; 0.01 g of citric acid was then added to obtain an acidic mixed solution, the pretreated ceramsite was added to the solution, and then slowly stirred at a speed of 90 r / min for 10 min, and the mixed solution was placed in a fume hood at room temperature of 25 ° C for 3 h, and stirred at a uniform speed of 5 min every 1 h, and the stirring speed was 90 r / min to ensure that the ceramsite and the polylactic acid solution were fully in contact and attached to obtain attached ceramsite;
[0026] S3. Post-treatment: Then put the attached ceramsite into an oven and bake it at 70°C for 1 hour to obtain the modified ceramsite.
[0027] Example 2
[0028] Preparation of modified porous ceramsite with sustained release function
[0029] S1. Pretreatment: screen porous ceramsite with a particle size of 2 mm, and wash the powder on the surface of the ceramsite with distilled water until the washing liquid is clear and free of impurities; weigh a certain amount of ceramsite and immerse it completely in distilled water, place it in an ultrasonic device, and ultrasonicate it for 30 minutes. During this period, stir it at a constant speed of 1 minute every 10 minutes, and the stirring speed is 90r / min; finally, put the ultrasonicated ceramsite into an oven and bake it at 100°C for 1 hour to obtain pretreated ceramsite;
[0030] S2. Modification: Preparation of polylactic acid coating solution: 5 g of polylactic acid was added to 100 ml of a mixed solvent of dichloromethane and ethanol and stirred to obtain a polylactic acid solution; 0.03 g of citric acid was then added to obtain an acidic mixed solution, the pretreated ceramsite was added to the solution, and then slowly stirred at a speed of 90 r / min for 10 min, the mixed solution was placed in a fume hood at room temperature of 25 ° C for 3 h, and stirred at a uniform speed of 5 min every 1 h, the stirring speed was 90 r / min, to ensure that the ceramsite and the polylactic acid solution were fully in contact and attached to obtain attached ceramsite;
[0031] S3. Post-processing: The attached ceramsite is then placed in an oven and baked at 70° C. for 1 hour to obtain the modified ceramsite.
[0032] Example 3
[0033] Preparation of modified porous ceramsite with sustained release function
[0034] S1. Pretreatment: screen porous ceramsite with a particle size of 2 mm, and wash the powder on the surface of the ceramsite with distilled water until the washing liquid is clear and free of impurities; weigh a certain amount of ceramsite and immerse it completely in distilled water, place it in an ultrasonic device, and ultrasonicate it for 30 minutes. During this period, stir it at a constant speed of 1 minute every 10 minutes, and the stirring speed is 90r / min; finally, put the ultrasonicated ceramsite into an oven and bake it at 100°C for 1 hour to obtain pretreated ceramsite;
[0035] S2. Modification: Preparation of polylactic acid coating solution: 5 g of polylactic acid was added to 100 ml of a mixed solvent of dichloromethane and ethanol and stirred to obtain a polylactic acid solution; 0.05 g of citric acid was then added to obtain an acidic mixed solution, the pretreated ceramsite was added to the solution, and then slowly stirred at a speed of 90 r / min for 10 min, the mixed solution was placed in a fume hood at room temperature of 25 ° C for 3 h, and stirred at a uniform speed of 5 min every 1 h, the stirring speed was 90 r / min, to ensure that the ceramsite and the polylactic acid solution were fully in contact and attached to obtain attached ceramsite;
[0036] S3. Post-treatment: Then put the attached ceramsite into an oven and bake it at 70°C for 1 hour to obtain the modified ceramsite.
[0037] Example 4
[0038] Preparation of modified porous ceramsite with sustained release function
[0039] S1. Pretreatment: screen porous ceramsite with a particle size of 2 mm, and wash the powder on the surface of the ceramsite with distilled water until the washing liquid is clear and free of impurities; weigh a certain amount of ceramsite and immerse it completely in distilled water, place it in an ultrasonic device, and ultrasonicate it for 30 minutes. During this period, stir it at a constant speed of 1 minute every 10 minutes, and the stirring speed is 90r / min; finally, put the ultrasonicated ceramsite into an oven and bake it at 100°C for 1 hour to obtain pretreated ceramsite;
[0040] S2. Modification: Preparation of polylactic acid coating solution: 5 g of polylactic acid was added to 100 ml of a mixed solvent of dichloromethane and ethanol and stirred to obtain a polylactic acid solution; 0.08 g of citric acid was then added to obtain an acidic mixed solution, the pretreated ceramsite was added to the solution, and then slowly stirred at a speed of 90 r / min for 10 min, the mixed solution was placed in a fume hood at room temperature of 25 ° C for 3 h, and stirred at a uniform speed of 5 min every 1 h, the stirring speed was 90 r / min, to ensure that the ceramsite and the polylactic acid solution were fully in contact and attached to obtain attached ceramsite;
[0041] S3. Post-treatment: Then, the attached ceramsite is placed in an oven and baked at 70°C for 1 hour to obtain the modified ceramsite comparative example 1.
[0042] S1. Pretreatment: screen porous ceramsite with a particle size of 2 mm, and wash the powder on the surface of the ceramsite with distilled water until the washing liquid is clear and free of impurities; weigh a certain amount of ceramsite and immerse it completely in distilled water, place it in an ultrasonic device, and ultrasonicate it for 30 minutes. During this period, stir it at a constant speed of 1 minute every 10 minutes, and the stirring speed is 90r / min; finally, put the ultrasonicated ceramsite into an oven and bake it at 100°C for 1 hour to obtain pretreated ceramsite;
[0043] S2. Modification: 0.01 g of citric acid was added to 100 ml of water to obtain an acidic solution, the pretreated ceramsite was added to the solution, and then slowly stirred at a speed of 90 r / min for 10 min, the mixture was placed in a fume hood at room temperature 25 ° C for 3 h, and stirred at a constant speed of 5 min every 1 h, the stirring speed was 90 r / min, to ensure that the ceramsite and the polylactic acid solution were fully contacted and attached to obtain attached ceramsite;
[0044] S3. Post-treatment: Then, the attached ceramsite is placed in an oven and baked at 70°C for 1 hour to obtain the modified ceramsite comparative example 2.
[0045] S1. Pretreatment: screen porous ceramsite with a particle size of 2 mm, and wash the powder on the surface of the ceramsite with distilled water until the washing liquid is clear and free of impurities; weigh a certain amount of ceramsite and immerse it completely in distilled water, place it in an ultrasonic device, and ultrasonicate it for 30 minutes. During this period, stir it at a constant speed of 1 minute every 10 minutes, and the stirring speed is 90r / min; finally, put the ultrasonicated ceramsite into an oven and bake it at 100°C for 1 hour to obtain pretreated ceramsite;
[0046] S2. Modification: 0.03 g of citric acid was added to 100 ml of water to obtain an acidic solution, the pretreated ceramsite was added to the solution, and then slowly stirred at a speed of 90 r / min for 10 min, the mixture was placed in a fume hood at room temperature 25 ° C for 3 h, and stirred at a constant speed of 5 min every 1 h, the stirring speed was 90 r / min, to ensure that the ceramsite and the polylactic acid solution were fully contacted and attached to obtain attached ceramsite;
[0047] S3. Post-treatment: Then, the attached ceramsite is placed in an oven and baked at 70°C for 1 hour to obtain the modified ceramsite comparative example 3.
[0048] S1. Pretreatment: screen porous ceramsite with a particle size of 2 mm, and wash the powder on the surface of the ceramsite with distilled water until the washing liquid is clear and free of impurities; weigh a certain amount of ceramsite and immerse it completely in distilled water, place it in an ultrasonic device, and ultrasonicate it for 30 minutes. During this period, stir it at a constant speed of 1 minute every 10 minutes, and the stirring speed is 90r / min; finally, put the ultrasonicated ceramsite into an oven and bake it at 100°C for 1 hour to obtain pretreated ceramsite;
[0049] S2. Modification: 0.05 g of citric acid was added to 100 ml of water to obtain an acidic solution, the pretreated ceramsite was added to the solution, and then slowly stirred at a speed of 90 r / min for 10 min, the mixture was placed in a fume hood at room temperature 25 ° C for 3 h, and stirred at a uniform speed of 5 min every 1 h, the stirring speed was 90 r / min, to ensure that the ceramsite and the polylactic acid solution were fully contacted and attached to obtain attached ceramsite;
[0050] S3. Post-treatment: Then, the attached ceramsite is placed in an oven and baked at 70°C for 1 hour to obtain the modified ceramsite comparative example 4.
[0051] S1. Pretreatment: screen porous ceramsite with a particle size of 2 mm, and wash the powder on the surface of the ceramsite with distilled water until the washing liquid is clear and free of impurities; weigh a certain amount of ceramsite and immerse it completely in distilled water, place it in an ultrasonic device, and ultrasonicate it for 30 minutes. During this period, stir it at a constant speed of 1 minute every 10 minutes, and the stirring speed is 90r / min; finally, put the ultrasonicated ceramsite into an oven and bake it at 100°C for 1 hour to obtain pretreated ceramsite;
[0052] S2. Modification: 0.08 g of citric acid was added to 100 ml of water to obtain an acidic solution, the pretreated ceramsite was added to the solution, and then slowly stirred at a speed of 90 r / min for 10 min, the mixture was placed in a fume hood at room temperature 25 ° C for 3 h, and stirred at a uniform speed of 5 min every 1 h, the stirring speed was 90 r / min, to ensure that the ceramsite and the polylactic acid solution were fully contacted and attached to obtain attached ceramsite;
[0053] S3. Post-treatment: Then, the attached ceramsite is placed in an oven and baked at 70°C for 1h to obtain modified ceramsite. The modified porous ceramsite obtained in Examples 1-4 and Comparative Examples 1-4 was tested. The test method is as follows: 5g of the modified porous ceramsite was immersed in 50ml of deionized water for 10min, and its initial pH was measured. Then, 10ml, 20ml, 20ml, 50ml, 50ml, and 50ml of deionized water were added thereto. Each time, it was gently stirred, and waited for 5min. The pH value was measured. The pH value was plotted against the amount of water added. The results are shown in the figure. Figure 1 , Figure 2 shown.
Claims
1. The present invention discloses a method for preparing modified porous ceramsite with a sustained-release function, characterized in that: The following steps are involved: S1 pretreatment: pretreating the ceramsite to obtain pretreated ceramsite; S2 modification: adding polylactic acid to a mixed solvent of dichloromethane and ethanol and stirring the mixture to obtain a polylactic acid solution; then adding citric acid to obtain an acidic mixed solution, and placing the pretreated ceramsite therein; S3 attachment: the mixed solution is intermittently allowed to stand and stirred at a constant speed, and then separated to obtain attached ceramsite; S4 post-processing: The attached ceramsite is left to stand and then dried to obtain the modified porous ceramsite product.
2. A method for preparing a modified porous ceramsite with a sustained-release function according to claim 1, characterized in that: The particle size of the modified expanded clay is 2 to 4 mm.
3. A method for preparing modified porous ceramsite with sustained release function according to claim 1, characterized in that: In S1, the pretreatment method is: wash the surface of the ceramsite with distilled water; immerse the ceramsite completely in distilled water, place it in an ultrasonic device, perform ultrasound and uniform stirring intermittently, and finally, dry the washed ceramsite to obtain the pretreated ceramsite.
4. A method for preparing modified porous ceramsite with sustained release function according to claim 1, characterized in that : In S2, the concentration of the polylactic acid solution is 10 to 50 g / L.
5. A method for preparing modified porous ceramsite with sustained release function according to claim 1, characterized in that : In S2, the concentration of the citric acid solution is 0.01g~10g / L.
6. A method for preparing modified porous ceramsite with sustained release function according to claim 1, characterized in that : In S2, the stirring speed is 120-200 r / min, and the stirring time is 10-20 min.
7. A method for preparing modified porous ceramsite with sustained release function according to claim 1, characterized in that : In S4, the drying temperature is 50-100°C.
8. An application of porous ceramsite prepared by the method for preparing modified porous ceramsite with sustained release function according to any one of claims 1 to 7, characterized in that: Porous ceramsite is used to balance the pH of water.
Citation Information
Cited By
Constructed wetland filter material and preparation method thereof
CN120247255A